Effect of Social Media Marketing Strategies on Competitive Advantage Among the SMEs in China - Chen, Yan Shiu; Lin, Huang Ha Lin (Journal of Marketing and Communication, 2021)
The competitive advantage is potent in facilitating the outsmarting of the competitors. Nonetheless, the competitive advantage of SMEs in China has been very poor. It is estimated that more than 41 percent of SMEs fail within four years after commencing operations. This study examined the effect of social media strategies on competitive advantage among SMEs in China. The study adopted the cross-sectional research design. This design was deemed significant since various SMEs in Beijing were used. The study used the purposive sampling technique to get the sample. This sampling design depends on the decision of the researcher. The researcher chose a sample that convenient to him or her for making the representation for analysis. The study found that social media marketing strategies is positively and significantly related to the competitive advantage. The study concluded that the application of social media marketing strategies in the current World is important for building the relationship between sellers and customers. The use of social media such as Facebook, Twitter and Instagram facilitate the interaction between sellers and consumers. The study further concluded that social media has become the most influential and important virtual space where the platform is not only used for social networking but is also a great way of digitally advertising your brand and your products. The application of social media in the current World is important for building the relationship between sellers and customers. Some of the social media been applied at large include Facebook, Twitter, Instagram and blogs. The study concluded that the use of social media enables the business to discover what society needs and increases brand awareness of the products and services. The study recommended that SMEs in China should use social media to market their products and services. The use of social media such as Facebook, Twitter and Instagram facilitate the interaction between sellers and consumers. The study further recommended that businesses should continue using social media platforms to increase the performance of companies and gain a competitive advantage in the long run. Keyword: Social Media Marketing Strategies, Competitive Advantage, SMEs, China